Vertical jump ability of elite volleyball players compared to elite athletes in other team sports - Kroon, S.
The focus of this literature review was to examine the available research relating to vertical jump ability of elite volleyball players, and to compare this with available data on other elite team sport athletes. The later part of the review will discuss some possible reasons for variations in vertical jump ability exhibited by athletes from different training backgrounds. Available literature supports the idea that different jumping styles and techniques exhibited between various sporting activities require very different strength properties and motor pattern development, for optimum performance (16,24,25,29,32). Throughout the literature there was strong evidence for the importance of the role of the arm swing(16), torso extension and head movements in V.J. performance, as well as the role of leg power in maximum extension(5,16,32).